Alcohol-related injury admission trends in adolescents: A comparison between Western Australia and England: IJPDS (2017) Issue 1, Vol 1:186, Proceedings of the IPDLN Conference (August 2016) - O'Donnell, Melissa; Sims, Scott; Maclean, Miriam; Gonzalez-Izquierdo, Arturo; Gilbert, Ruth; Stanley, Fiona (International Journal of Population Data Science, 2017)
ABSTRACT Objectives This study aims to determine trends in hospital admissions for alcohol-related injuries among young people in Western Australia and England and whether these admissions are intentionally or unintentionally caused. In addition, this study examines variation in trends by sex and age-groups to determine groups most at risk. Approach Annual incidence rates for alcohol-related injury rates were calculated using hospital admissions data for Western Australia and England. We compared trends in different types of alcohol-related injury by age and gender. Results Alcohol-related injuries have increased significantly from 1980-2009 (from 2 to 12 per 10,000). Conversely, alcohol-related injury rates have declined in England since 2007. In England self-harm is the most frequently recorded cause of alcohol-related injury. In Western Australia, unintentional injury is most common, however violence-related harm is increasing for boys and girls. Boys aged 16-17 in Western Australia had the highest rate of alcohol-related injury (27.1/10,000), which was markedly higher than for 16-17 year old girls in Western Australia (16.6/10,000), girls in England (14.1/10,000), or boys in England (13.2/10,000). Conclusion Alcohol-related harm is a significant public health issue, and in Western Australia there is a concerning trend of increasing alcohol-related injuries among young people. Alcohol-related harm of sufficient severity to require hospital admission is increasing among adolescents in Western Australia. Declining trends in England suggests this trend is not inevitable or irreversible. More needs to be done to address alcohol-related harm, and ongoing monitoring is required to assess the effectiveness of strategies.